Emoji literacies: Read & write, translate, montage - De la Rosa Carrillo, Ernesto Leon Gustavo (International VIsual Literacy Association, 2018)
Emoji literacy is explored as a particular brand of digital visual literacy through three distinct lesson plans developed within different contexts that focus on the expressive potential of these colorful pictographs. Largely unconcerned with the concrete communication afforded by alphabetical characters, each exploration revels on the ambiguity of emoji phrases that refuse to be simply read and demand to be interpreted, perhaps even translated into intellectual experiences that might deviate from the affective dimensions traditionally associated with them. The first lesson plan was specifically designed to take advantage of emoji possibilities as storytelling devices with 6 and 7-year-olds, whose reading and writing skills might still be developing. The second case was developed with young slam poets to explore the expressive limits of pictographs meant to instantly convey “thoughts or emotions without inspiring strong likes or dislikes” (Nageshi, 2014). Finally, a group of visual arts undergrads participated in the third emoji plan, which expanded on Eisenstein's Montage Theory as discussed in his seminal 1929 essay, The cinematographic principle and the ideogram. Together, these three emoji lessons trace a map that is not meant to quantify and exhaust emoji use in everyday conventional communication but to expand emoji literacy beyond the reaches of the written word and render it capable of fashioning its own poetic, creative and expressive dimensions that can only be fully interrogated within the art classroom.